MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN SELF-CONCEPT MAHASISWA PADA MATA KULIAH STATISTIKA PENDIDIKAN - Z, Yulia Rahmawati; Suriani, Teni (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
This research is motivated by the demands of learning in the 21st century which requires students and prospective mathematics teachers to have critical thinking skills. In fact, many students do not understand the rules in using the data processing principle and still make many mistakes in processing the research data they conduct. This research is a Classroom Action Research was conducted in the Educational Statistics course, Mathematics Education Study Program, Tamansiswa Padang University. Based on the results of the study, it can be concluded that: (1) The use of the PBL model can improve the mathematical critical thinking ability of students who take the Educational Statistics course for the 2023/2024 Academic Year. This can be proven through the final test with the average student score in cycle 1 of 70.77 increasing to 85 in cycle 2; (2) The use of the PBL Model can improve students' self-concept and learning activities. This can be evidenced by the percentage of student activity in cycle 1 of 66.59%, increasing to 71.02% in cycle 2.